2015
DOI: 10.1590/s1980-65742015000200002
|View full text |Cite
|
Sign up to set email alerts
|

The role of emotions on consumers' satisfaction within the fitness context

Abstract: Abstract-Previous studies have suggested that consumption-related emotions are important to understand post-purchase reactions. This study examines the relationship between fitness consumers' emotions and overall satisfaction. After an initial step of free-thought listing and content validity, followed by a pre-test, a survey was conducted among consumers of five different fitness centers (n=786). The questionnaire included measures to assess positive and negative emotions, as well as overall satisfaction with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 48 publications
(93 reference statements)
2
21
0
Order By: Relevance
“…Therefore, in the literature, during the last decades, management models such as perceived quality, satisfaction or perceived value have been commonly used to predict costumers' future intentions. However, for some time now, there have been variables in different studies that are becoming vitally important in predicting future intentions, among which, we find the emotions-related variables (Pedragosa et al, 2015;Molina et al, 2016;Ong and Yap, 2017). Likewise, these different studies have focused on analyzing, through Mean 35,89 361940,89 17,54 18774,54 327,80 22390606,11 5980,56 3110,27 SD 14,53 362997,07 5,70 20976,66 197,81 28275760,86 4894,99 3649,48 Minimum 18 1 1 1 8 4500 36 9 Maximum 77 1562500 25 78125 625 100000000 15625 15625 Percentiles 10 20 46210,2 9 1728 81 838635 1116 404 50 32 245367,5 16 11520 256 10266480 4096 1728 90 58 886936,25 25 50000 625 66249000 15625 7500 SD, standard deviation; SQ, service quality; SAT, satisfaction; PV, perceived value; FI, future intentions; SWB, subjective well-being.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Therefore, in the literature, during the last decades, management models such as perceived quality, satisfaction or perceived value have been commonly used to predict costumers' future intentions. However, for some time now, there have been variables in different studies that are becoming vitally important in predicting future intentions, among which, we find the emotions-related variables (Pedragosa et al, 2015;Molina et al, 2016;Ong and Yap, 2017). Likewise, these different studies have focused on analyzing, through Mean 35,89 361940,89 17,54 18774,54 327,80 22390606,11 5980,56 3110,27 SD 14,53 362997,07 5,70 20976,66 197,81 28275760,86 4894,99 3649,48 Minimum 18 1 1 1 8 4500 36 9 Maximum 77 1562500 25 78125 625 100000000 15625 15625 Percentiles 10 20 46210,2 9 1728 81 838635 1116 404 50 32 245367,5 16 11520 256 10266480 4096 1728 90 58 886936,25 25 50000 625 66249000 15625 7500 SD, standard deviation; SQ, service quality; SAT, satisfaction; PV, perceived value; FI, future intentions; SWB, subjective well-being.…”
Section: Discussionmentioning
confidence: 85%
“…On the other hand, few studies have been found that focus on sports centers, although there have been recent studies (Biscaia et al, 2012;Molina et al, 2016) analyzing psychological variables, such as life satisfaction, happiness, subjective well-being, and emotions, and their influence on customers' perceptions of a service. Pedragosa et al (2015) argue that both positive and negative emotions influence customer satisfaction and, consequently, influence future behavioral intentions. Similarly, Ong and Yap (2017) analyze the perceptions of customers of fitness centers in Malaysia, stating that the emotional response seems to have a stronger positive relationship with the behavioral intentions of customers.…”
Section: Introductionmentioning
confidence: 99%
“…A gym manager (general or technical) have to collect the participants perception of the service, listen their opinions and provide regular training to staff members, in order to increased levels of overall satisfaction (Pedragosa, Biscaia, & Correia, 2015). Have also to create a pleasant environment and provide a personalized service considering the participants goals, in order to improve the well-being feeling in the gym (Gonçalves, Biscaia, Correia, & Diniz, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Advances in the theory confirm that wine tourist perceive positive and negative attitudes in terms of demography, related to gender, age and highest level of studies achieved (e.g., Ahmed, 1986;Korça, 1998;McGehee & Andereck, 2004;Perdue, Long, P. T., & Allen, 1990;Tomlijenovic & Faulkner, 1999;Xu et al, 2016), which translate into positive and negative effects on the buying intent (Pedragosa, Biscaia & Correia, 2015; Pelegrín-Borondo, Arias-Oliva & Olarte-Pascual, 2016). Consequently, changes in the voluntary consumer behavior arise (Troung & Hall, 2016) because of marketing carried out by the companies in order to generate brand recognition of food and drink items (Vieira, López-Guzmán & Rodríguez, 2013).…”
Section: Wine Tourism and Marketingmentioning
confidence: 92%